Sacrifice and the limits of sovereignty 1589-1613 - Mortimer, S (Taylor & Francis, 2023)
Although sovereign power is often defined as transcending legal and religious norms, the work of historians like Prodi and Agamben has drawn our attention to the ways in which modern accounts of sovereignty depend fundamentally upon the fusion and transformation of these norms. In Latin Christendom, this process was enabled by the juridical quality of ecclesiastical authority, its expression through laws similar in form and structure to those of civil power. There was, however, an important strand of Catholic thinking from the late-sixteenth century which emphasised the centrality of sacrifice, rather than law or jurisdiction, in creating communities. For Catholic polemicists like Rossaeus (William Reynolds) sacrifice came before law and the juridical organisation of human society was secondary to the ritual and ceremonial. This article will examine the roots of this claim in post-Tridentine discussions of the Mass as a sacrifice and will go on to show how it was used to defend the primacy of the Catholic Church, particularly in 1590s France. It will consider the impact of this argument and suggest its importance in provoking new and more powerful articulations of both royal sovereignty and papal power.